How Does Performance Feedback Affect Boundary Spanning in Multinational Corporations? Insights from Technology Scouts. (26th January 2017) - Klueter, Thomas; Monteiro, Felipe
Abstract: As much as prior research has shed light on the boundary‐spanning processes of global organizations and their (positive) impact on an MNC's performance, whether, when and how past performance ultimately shapes an MNC's boundary‐spanning activities remains an open question in management research. To tackle these questions, we examine the behaviour of technology scouts in global organizations who span organizational and national boundaries to tap into novel knowledge and span internal boundaries to present this knowledge to constituents inside the MNC. Drawing on the behavioural theory of the firm, we propose that the intensity of organizational boundary spanning, the likelihood of spanning national boundaries and the way technology scouts span internal boundaries to engage with members inside the organization are sensitive to how the MNC has performed relative to its aspirations. We support our theoretical expositions with insights gained from interviewing senior industry professionals with direct experience in technology scouting in MNCs.